Declaration of the Council of Heads and Heads of State and Government of the Union of South American Nations (UNASUR) - Suramericanas, Unión de Naciones (2013)
Council of Heads and Heads of State and Government of UNASUR, meeting in extraordinary session in Lima on April 18, 2013, agrees to appoint a UNASUR Commission to accompany the investigation of the violent events of April 15, 2013.